IMPLEMENTASI STRATEGI PEMBELAJARAN PRODI PENDIDIKAN BAHASA ARAB IAIN SAMARINDA 2018 - Edy Murdani Z (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2018)
This study aims to explore information about the implementation of learning strategy of Arabic education program IAIN Samarinda, the object of this study are lecturers who teach on arabic education study program that is determined by using purposive sampling, in this study, researchers used interview techniques, observation and documentation, while the research desainused is a qualitative approach with the result of a description that aims to find the pattern of information obtained in the field In this case, the result of the research is (1) Impelementation of learning strategy in IAIN Samarinda arabic study program runs well which is normative implementation, it is shown by the implementation of learning that has been done by the lecturer of course runs according to its function, such as preparing syllabus and learning tools, using strategies and techniques in teaching, and evaluating at the end of the course. (2) The strategy used in learning in IAIN Samarinda arabic education program is active learning for speaking skill, cooperative learning for skill, qowaid wa tarjamah for learning element of language of nahwu, shorof and tarjamah, and for reading skill is qiraah shomitah and jahriyah, drill and awlawiyat for writing skills. (3) Factors supporting the implementation are: a. Able to prepare instructional devices at each meeting b. Pengampu determine appropriate strategies and techniques in adjusting teaching materials c. The availability of learning media well (4) The inhibiting factor of the implementation is the learning is a. Qualification of students, so the implementation of the strategy must be really on target and adjust the cognitive level of students b. Distribution of courses not all speak Arabic